Effectiveness of Topical Microbiome Containing Lactococcus Ferment Lysate 5% in Acne Vulgaris Patients - Anwar, Anis Irawan; Zainuddin, Andi Alfian; Hutabarat, Emma Novauli; Savitri, Ketut Alit Pinidha (Journal of Pakistan Association of Dermatologists, 2025)
Background: Acne vulgaris is a type of persistent inflammatory dermatosis and can be manifested on varying levels, ranging from mild to very severe, but even moderate cases can cause psychological and emotional suffering. Several skin microbiomes are involved in the pathophysiology of acne vulgaris, and alterations in the microbiome composition (dysbiosis) will contribute to the breakdown of the skin barrier as well as immunological activation and inflammation. Lactococcus ferment lysate is a probiotic that has been shown to have anti-inflammatory properties. Topical probiotic treatments are considered safe and without adverse effects, when compared to topical and systemic standard therapies. Objective: The purpose of this study was to investigate the efficacy of treating acne vulgaris with a microbiome comprising 5% Lactococcus ferment lysate. Methods: The study employed a double-blind randomized controlled trial design. A total of 70 research participants were separated into two groups: placebo (A) and therapy (B). To determine the correlation between the two variables, the Pearson correlation test was used. Results: The average number of lesions in the intervention group decreased from 48.5 (before intervention) to 24.5 (after intervention). Furthermore, it was discovered that lowering sebum levels on the forehead (week-6) and cheeks (week-8) was more effective in the intervention group than in the control group (placebo). Pro-inflammatory cytokines (IL-12, IL-8, and TNF-a) decreased in both the treatment and placebo groups, but not significantly (P > 0.05). Conclusion: It has been demonstrated that topical microbiomes containing 5% Lactococcus ferment lysate lower the severity of acne vulgaris, sebum levels, pro-inflammatory cytokines, and enhance anti-inflammatory cytokines.